The Implementation of Guided Inquiry Learning Model to Improve Students’ Creative Thinking Skills in Physics - Nurulwati Nurulwati; Musdar Musdar; Mawarni Saputri (Postgraduate, University of Mataram, 2023)
The aim of this research was to find out the improvement of students' creative thinking skills by using guided inquiry learning model. The research was classroom action research which held on 3 cycles. Each cycle consisted of four steps that are Planning, Action, Observation, and Reflection. The data collecting technique was carried out through ten creative thinking skills tests in essay form and also questionnaire to evaluate students’ response to the learning activities. An expert validation test was first was first run before the instrument test was tested on the students. Analysis data technique used descriptive analysis. The results of research showed that there was an improvement in each of these aspects of students’ creative thinking skill from cycle I, cycle II until the cycle III. Average percentage improvement of students' creative thinking skills where the highest indicator score was fluency while the highest score attitude aspect of creative thinking was curiosity. From the result, it can be concluded that guided inquiry learning was able to improve students' creative thinking skills especially in physics